Rządy księżnej kujawskiej Eufrozyny na Kujawach po śmierci Kazimierza kujawskiego (1267-1275) (Kronika Bydgoska, 2018)
This article describes the caring rule of Duchess Euphrosyne, the widow of Casimir I of Kuyavia, in the period after the death of her first husband, between1267 and 1275. The period of reign of Euphrosyne, Duchess of Opole and Kuyavia, a daughter of Casimir I of Opole and his wife Viola that lasted until 1275, is known as the carrying rule. She followed in her mother’s footsteps, who after the death of Casimir I of Opole ruled the duchy on behalf of her sons. In 1275, Ladislaus I the Elbow-high issued his first document, in which he mentions his mother’s approval. After that year, she left Kuyavia and departed to Pomerania. Duchess Euphrosyne was ruling over the land of Brest of Kuyavia, the Duchy of Łęczyca and the land of Dobrzyń. Boleslaus the Pious was helping Euphrosyne and her sons during her time in power. Euphrosyne was surely ruling the area in 1267-1275, since it is confirmed by documents issued by the duchess herself, her son Ladislaus and Boleslaus the Pious. Historians have different interpretations for the duchess’s rule, some describe it as weak, and some perceive it as rigid. Information about the rules of Euphrosyne is rather limited; there are only two documents issued by Euphrosyne that have been preserved, making it difficult to describe her reign in Kuyavia.